Preparation and application of efficient organic-inorganic hybrid fireproof coating
By using organic-inorganic hybrid fire-retardant coatings of polyhydroxy flame retardant copolymers and inorganic flame retardant and smoke-retardant nanomaterials on rigid polyurethane foam, the existing coatings have been solved, with high cost, high toxicity and poor flame retardant. It achieves low-cost, environmentally friendly and efficient flame retardant effects.
Patent Information
- Application Number
- CN202411571706.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The fire-retardant coating of existing rigid polyurethane foams is costly, has high toxicity and poor flame retardancy, making it difficult to meet the needs of low-cost, environmentally friendly and efficient flame retardant.
The organic-inorganic hybrid fire-retardant coating is prepared by combining polyhydroxy flame retardant copolymers with inorganic flame retardant and smoke-retardant nanomaterials through solution blending. The transition metal oxides are loaded with hexagonal boron nitride and eloite nanotubes to enhance the Flame retardant efficiency and material controllability.
It realizes a low-cost, environmentally friendly and efficient flame retardant coating, with excellent flame retardant properties, good water solubility and good mechanical strength, and is suitable for flame retardant materials of rigid polyurethane foam.
Smart Images

Figure CN119505609A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fire-retardant coatings, and in particular relates to the preparation and application of a high-efficiency organic-inorganic hybrid fire-retardant coating. Background Art
[0002] Rigid polyurethane (PU) foam has excellent properties such as good insulation, light weight, high specific strength, and convenient construction. It also has the characteristics of sound insulation, shock resistance, electrical insulation, heat resistance, cold resistance, and solvent resistance. It is widely used in the insulation layer of refrigerators and freezers, cold storage, refrigerated trucks and other insulation materials, buildings, storage tanks and pipeline insulation materials, and a small amount is used in non-insulating occasions, such as imitation wood, packaging materials, etc. However, rigid polyurethane foam is a flammable material that may burn rapidly when it comes into contact with a fire source. Once burned, it may cause a fire and endanger the safety of life and property. Therefore, the fire resistance of rigid polyurethane is crucial to ensure building safety, meet regulatory requirements, improve material durability, and protect the environment.
[0003] Inspired by organisms such as snails and tree frogs, Ma et al. showed strong adhesion to the surface of materials through interfacial hydrogen bonds and physical adhesion, and designed a flame-retardant polymer coating with phase-separated micro / nanostructure through simple free radical copolymerization (Acs Nano, 2021, 15.7, 11667-11680). Organic-inorganic hybrid materials have been developed and reported as flame retardant research. Hexagonal boron nitride has a two-dimensional nanostructure, a very high surface area, high flame retardant efficiency, moderate price and high thermal stability; natural mineral halloysite nanotubes are cheap, have excellent performance and abundant resources. Both materials can be used as ideal carriers for loading nanoadditives and as a powerful barrier to prevent the agglomeration of loaded nanoadditives. Therefore, in the polymer matrix, the dispersion of nanohybrids is better than that of individual materials, that is, loading nanoadditives at the inorganic level is an effective solution to improve the dispersion of individual carriers in the polymer matrix.
[0004] Publication No. CN118005882A reports a highly flame-retardant polyurethane rigid foam insulation material. Compared with traditional bromine-based flame retardants, the miscibility of liquids greatly improves the dispersion of bromine elements in the material, the synergistic flame retardancy of nitrogen elements, greatly reduces the amount of bromine used, reduces the flame retardant cost, and solves the problem of its dispersed storage and use. Publication No. CN116284988A reports a method for preparing an organic-inorganic hybrid flame-retardant nano coating and its application in soft polyurethane surface foam. By utilizing the acid and alkali corrosion resistance of amino carbon nanotubes and the high reactivity of phosphate and amino groups of phytic acid, the surface of the soft polyurethane foam is first modified with amino carbon nanotubes to form a protective layer and give it multiple reactive sites; then, the phytic acid is grafted onto the amino carbon nanotubes through a salt-forming reaction, and an organic-inorganic hybrid surface flame retardant coating is constructed on the surface of the soft polyurethane foam to obtain a flame-retardant soft polyurethane foam with high flame retardant properties. However, the research on flame retardant coatings based on rigid polyurethane foam still has problems such as high cost, high toxicity, and poor flame retardancy. Therefore, designing a low-cost halogen-free organic-inorganic hybrid fire retardant coating has important practical application value. Summary of the invention
[0005] The present invention aims to solve the problems of high cost, high toxicity, poor flame retardancy and the like of fire retardant coatings for combustible substrates, and provides a method for preparing and applying a highly efficient organic-inorganic hybrid fire retardant coating, wherein the coating comprises an organic polyhydroxy flame retardant copolymer and an inorganic flame retardant and smoke suppressing nanomaterial. The fire retardant coating of the present invention has excellent flame retardant properties and good water solubility, and is pollution-free to the environment and human body. The preparation process of the fire retardant coating of the present invention is low in cost, simple and green in operation, highly controllable, and can be prepared in batches.
[0006] In the present invention, unlike traditional flame retardants that contain a large amount of toxic elements, which may have a negative impact on the environment and health, and may release a large amount of toxic gases during fire combustion, the polyhydroxy flame retardant copolymer, as a water-based flame retardant polymer coating, has high adhesion and flame retardancy, and is soluble in water, and will not have a negative impact on the environment during the preparation and combustion processes. In addition, the present invention designs an organic / inorganic hybrid method that utilizes hydroxyl-containing biomass molecules and transition metal oxides to achieve a high efficiency improvement in flame retardant efficiency, and achieves a balancing process of synergistic flame retardancy and other properties. The above technologies are the key to preparing high-efficiency flame retardant coating materials that are low-cost, simple and green to operate, low-cost, highly controllable, and highly flame-retardant.
[0007] The method for preparing the high-efficiency organic-inorganic hybrid fire-retardant coating of the present invention comprises the following steps: Step 1: Preparation of polyhydroxy flame retardant copolymer Based on the ionic flame retardant comonomer sodium styrene sulfonate, it is copolymerized with hydroxyl-containing biomass molecules to prepare a polyhydroxyl flame retardant copolymer by free radical solution polymerization.
[0008] In step 1, the hydroxyl-containing biomass molecules are slowly added dropwise to an aqueous solution of sodium styrene sulfonate, heated under stirring for reaction, and then a deionized aqueous solution of potassium persulfate is added dropwise to the system to prepare a polyhydroxy flame-retardant copolymer. In order to obtain an aqueous solution with a controllable solid concentration, dialysis and drying are used to remove the remaining monomers and excess water.
[0009] Furthermore, the hydroxyl-containing biomass molecule is hydroxybutyl acrylate or hydroxypropyl methacrylate.
[0010] Furthermore, the feed ratio of hydroxyl-containing biomass molecules to sodium styrene sulfonate is in the range of 0.5:1-1:1, and the feed ratio of sodium styrene sulfonate to potassium persulfate is in the range of 80:1-100:1.
[0011] Furthermore, the polymerization reaction temperature is 60-70°C, and the heating rate is 5-20°C / min.
[0012] Furthermore, the mechanical stirring speed is controlled at 200-500 rpm, and the polymerization time is 1-6 h.
[0013] Furthermore, the size of the dialysis bag is 36 mm-70 mm, the solid content of the polyhydroxy flame-retardant copolymer obtained by dialysis is 10-30 wt %, and the number average molecular weight of the obtained polyhydroxy flame-retardant copolymer is controlled between 200,000 and 300,000.
[0014] Step 2: Loading of transition metal oxides Hexagonal boron nitride and halloysite nanotubes loaded with transition metal oxide nanomaterials were prepared by impregnation method.
[0015] Specifically, the metal salt precursor is dispersed in deionized water, hexagonal boron nitride or halloysite nanotubes are added, ammonia water is used as a precipitant, and the reaction is stirred at room temperature to complete the loading of the active component; after the reaction is completed, centrifugation, washing and drying are performed, and hexagonal boron nitride-loaded transition metal oxide nanomaterials or halloysite nanotube-loaded transition metal oxide nanomaterials are obtained after calcination.
[0016] Furthermore, the metal salt precursor is one or more of nickel chloride and sodium molybdate; the concentration of the metal salt precursor solution is in the range of 0.5 mol / L-1 mol / L.
[0017] The transition metal oxide is one or more of nickel oxide and molybdenum oxide. The content of the active component transition metal oxide in the carrier ranges from 5wt% to 10wt%.
[0018] Further, aqueous ammonia was added until the pH of the system reached ≥9.
[0019] Furthermore, the size of hexagonal boron nitride is controlled to be 1-30 μm. The surface of hexagonal boron nitride is functionalized by ball milling before use, and the ball milling time is 2-6 hours. The hexagonal boron nitride powder after ball milling is dispersed by ultrasound, and the mass ratio of the mixed powder and deionized water is in the range of 1:20 to 1:100.
[0020] Furthermore, the diameter of the halloysite nanotubes is in the range of 50-200 nm, and the length is in the range of 200 nm-1 μm.
[0021] Furthermore, the stirring reaction time is 1-6 hours, and the stirring speed is controlled at 300-600 rpm.
[0022] Furthermore, the calcination temperature is 400-800°C; and the calcination time is 6-12 h.
[0023] In the hexagonal boron nitride loaded transition metal oxide nanomaterial or the halloysite nanotube loaded transition metal oxide nanomaterial obtained in this step, the mass ratio of the hexagonal boron nitride or halloysite nanotube to the transition metal oxide is 10:1 to 20:1.
[0024] Step 3: Preparation of composite coating Using deionized water as a dispersion medium, hexagonal boron nitride-loaded transition metal oxide nanomaterials and / or halloysite nanotube-loaded transition metal oxide nanomaterials are added to the polyhydroxy flame-retardant copolymer obtained in step 1 by solution mixing to obtain an organic-inorganic hybrid coating slurry; the obtained coating slurry is applied to the surface of a base material, and a flame-retardant nanocomposite coating is obtained after drying.
[0025] Furthermore, the mass ratio of the hexagonal boron nitride-loaded transition metal oxide nanomaterial and / or the halloysite nanotube-loaded transition metal oxide nanomaterial to the mass ratio of the polyhydroxy flame-retardant copolymer is 1:10 to 1:20.
[0026] Furthermore, the drying temperature is 60-100°C and the drying time is 6-12 h.
[0027] Furthermore, the solid content of the coating on the surface of the substrate is in the range of 3 g / dm 3 -6 g / dm 3 The invention relates to the use of the high-efficiency organic-inorganic hybrid fireproof coating in the preparation of flame-retardant rigid polyurethane foam materials.
[0028] Specifically, the rigid polyurethane foam is used as the base material, the organic-inorganic hybrid coating slurry is coated on the surface of the base material, and the flame-retardant rigid polyurethane foam material can be obtained after drying.
[0029] The beneficial effects of the present invention are as follows: (1) The preparation process of the polyhydroxy flame-retardant copolymer is simple and green, and does not involve the use of any harmful reagents. (2) Hexagonal boron nitride with high flame retardant efficiency, moderate price and high thermal stability and natural mineral halloysite nanotubes with low price, excellent performance and abundant resources are selected as nano-carriers, and the preparation method of the loaded transition metal oxide nanomaterial has the advantages of low cost, strong controllability and batch preparation. (3) The prepared fire-retardant coating has good mechanical strength (shear strength is about 0.2MPa). (4) The fire-retardant coating has excellent flame retardancy and can be used as an ideal flame retardant material for rigid polyurethane foam. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the NMR spectrum of the polyhydroxy flame retardant copolymer prepared by addition polymerization of sodium styrene sulfonate and hydroxybutyl acrylate in Example 1.
[0031] Figure 2 This is the NMR spectrum of the polyhydroxy flame retardant copolymer prepared by addition polymerization of sodium styrene sulfonate and hydroxypropyl methacrylate in Example 2.
[0032] Figure 3 This is a scanning electron microscope image of transition metal oxide-supported hexagonal boron nitride and halloysite nanotubes prepared by the impregnation method in Example 5.
[0033] Figure 4 This is a transmission electron micrograph of the transition metal oxide-supported hexagonal boron nitride and halloysite nanotubes prepared by the impregnation method in Example 5.
[0034] Figure 5 This is the X-ray diffraction pattern of the transition metal oxide-supported hexagonal boron nitride and halloysite nanotubes prepared by the impregnation method in Example 5.
[0035] Figure 6 The microcalorimeter test results of the rigid polyurethane foam with flame retardant coating prepared in Example 6 at 35 kW.
[0036] Figure 7 The microcalorimeter test results of the rigid polyurethane foam with flame retardant coating prepared in Example 6 at 50 kW.
[0037] Figure 8 This is the cone calorimeter test result of the rigid polyurethane foam with the flame retardant nanocomposite coating prepared in Example 6 at 35 kW.
[0038] Fig. 9 The cone calorimeter test result of the rigid polyurethane foam with the flame retardant nanocomposite coating prepared in Example 6 at 50 kW.
[0039] Fig.10This is the cone calorimeter test result of the rigid polyurethane foam with the flame retardant nanocomposite coating prepared in Example 6 at 75 kW.
[0040] Fig.11 The smoke test results at 25 kW for the rigid polyurethane foam with the flame retardant nanocomposite coating prepared in Example 6 are shown in FIG.
[0041] Fig.12 The toxicity test results of the rigid polyurethane foam with the flame-retardant nanocomposite coating prepared in Example 6 at 25 kW are shown.
[0042] Fig.13 This is a scanning electron microscope image of carbon residue after combustion of the rigid polyurethane foam with the flame-retardant nanocomposite coating prepared in Example 6. DETAILED DESCRIPTION
[0043] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, the purpose of which is to explain the content of the present invention more specifically and clearly rather than to limit the protection scope of the present invention. Embodiment 1:
[0044] Sodium styrene sulfonate and hydroxybutyl acrylate are subjected to addition polymerization in a four-necked round-bottom flask equipped with a stirrer, a condenser and a thermometer.
[0045] 30.2 g of hydroxybutyl acrylate was slowly added to a 500 mL four-necked round-bottom flask containing 130 g of sodium styrene sulfonate aqueous solution (25 wt%) and 24.9 g of deionized water, and then heated to 65 °C in a water bath with mechanical stirring at 300 rpm for 3 h. After mixing evenly, 60.9 g of deionized water containing 0.55 g of potassium persulfate was added dropwise to the mixture at a rate of 60 mL min -1 After the mixed solution was stirred for 5 h, 0.065 g potassium persulfate was subsequently added to the solution and the polymerization was continued at 65 °C, with a rotation speed of 300 rpm and a stirring time of 1 h. In order to obtain an aqueous solution with a controllable solid concentration, dialysis and drying were used to remove the remaining monomers and excess water. Embodiment 2:
[0046] Sodium styrene sulfonate and hydroxypropyl methacrylate were subjected to addition polymerization in a four-necked round-bottom flask equipped with a stirrer, a condenser and a thermometer.
[0047] 32.4 g of hydroxypropyl methacrylate was slowly added to a 500 mL four-necked round-bottom flask containing 130 g of sodium styrene sulfonate aqueous solution (25 wt%) and 24.9 g of deionized water, and then heated to 65 °C in a water bath with mechanical stirring at 300 rpm for 3 h. After mixing evenly, 60.9 g of deionized water containing 0.55 g of potassium persulfate was added dropwise to the mixture at a rate of 60 mL min -1 After the mixed solution was stirred for 5 h, 0.065 g of potassium persulfate was subsequently added to the solution and the polymerization was continued at 65 °C, with a rotation speed of 300 rpm and a stirring time of 1 h. In order to obtain an aqueous solution with a controllable solid concentration, a dialysis and drying process was used to remove the remaining monomers and excess water. For comparison, homopolymer PHEA was also synthesized by the same synthesis method. Example 3: Surface functionalization of hexagonal boron nitride
[0048] Ball milling of hexagonal boron nitride to achieve surface functionalization of boron nitride: 1. Mix 10g of tannic acid powder and 20g of hexagonal boron nitride (size 30 μm) powder, place in a 300ml ball mill, the mass ratio of powder raw material to agate ball milling beads is 1:6, and perform ball milling at a ball milling speed of 400rpm for 10h.
[0049] 2. Disperse the above mixed powder in deionized water for ultrasonic treatment. The mass ratio of the mixed powder to deionized water is 1:20; the ultrasonic power is 200 KW, and the ultrasonic time is 20 min.
[0050] 3. The mixed solution was centrifuged and washed three times at a centrifugal speed of 10,000 rpm and a centrifugal time of 10 min to remove free TA, and the centrifugal operation was repeated until the supernatant was colorless and transparent. Finally, the white boron nitride nanosheet precipitate was prepared as an aqueous dispersion for further use. Example 4: Purification of Halloysite Nanotubes (HNTs)
[0051] 1. Stir 10 g of HNTs in 200 mL of deionized water vigorously for 1 h at 500 rpm to make a suspension.
[0052] 2. After the suspension has been allowed to stand for 5-10 min, discard the upper sediment and impurities and retain the middle portion where the HNTs are fully dispersed. Repeat the above washing steps three times.
[0053] 3. Add sodium hydroxide to the resulting suspension, adjust the pH to about 8.5, stir for 9 hours at 300 rpm, and let stand for 3 hours.
[0054] 4. The mixed solution was washed by centrifugation for 3 times at a speed of 10,000 rpm and a centrifugation time of 5 min. The precipitate was washed with clean water for 3 times and then freeze-dried. These HNTs were used in the subsequent preparation process. Embodiment 5:
[0055] Transition metal oxide supported hexagonal boron nitride (BN) and halloysite nanotubes (HNTs) hybrid nanomaterials were prepared by impregnation method.
[0056] 1. Disperse the transition metal salt nickel chloride evenly in the aqueous solution to prepare a transition metal salt aqueous solution with a concentration of 1 mol / L.
[0057] 2. Mix the prepared hexagonal boron nitride aqueous dispersion and transition metal salt solution, and stir magnetically at room temperature for 4 hours at a rotation speed of 500 rpm.
[0058] 3. Slowly add the ammonia solution to the mixed solution until the pH is greater than or equal to 9. After the addition, stir magnetically at room temperature for 4 hours at a speed of 300 rpm to complete the surface loading of the active component.
[0059] 4. The mixed solution was centrifuged and washed three times at a speed of 6000 rpm and a centrifugal time of 10 min. The centrifugal operation was repeated until the pH was neutral. Finally, the precipitate was dried in an oven at a temperature of 80°C for 12 h.
[0060] 5. The dried sample was calcined in a muffle furnace for 8 h at a temperature of 700°C to obtain hexagonal boron nitride loaded transition metal oxide nanomaterials. The amount of metal oxide loaded on the nanomaterials was 5wt%-10wt%.
[0061] The preparation method of the transition metal oxide nanomaterial loaded with halloysite nanotubes is the same as above, except that the hexagonal boron nitride is replaced by the halloysite nanotubes.
[0062] The transition metal salt nickel chloride was replaced by sodium molybdate, and other parameters remained unchanged, and the above process was repeated. Embodiment 6:
[0063] The hexagonal boron nitride loaded transition metal oxide nanomaterial or the halloysite nanotube loaded transition metal oxide nanomaterial is dispersed in the flame retardant copolymer coating by solution mixing to prepare the flame retardant nano composite coating.
[0064] 1. Disperse the hexagonal boron nitride-loaded transition metal oxide nanomaterials or halloysite nanotube-loaded transition metal oxide nanomaterials in deionized water for dispersion treatment. The mass ratio of the hexagonal boron nitride-loaded transition metal oxide nanomaterials or halloysite nanotube-loaded transition metal oxide nanomaterials to deionized water is 1:10; the stirring speed is 300 rpm; and the dispersion time is 30 min.
[0065] 2. Mix 20 mL of the above dispersion with a concentration of 0.1 g / mL and 500 g of a viscous solution of a polyhydroxy flame-retardant copolymer with a solid content of 20 wt%, and mechanically stir at room temperature for 2 h at a speed of 300 rpm to form an organic-inorganic hybrid mixed solution to prepare a flame-retardant nanocomposite coating.
[0066] 3. Next, the uniform mixed solution is coated on the surface of the rigid polyurethane foam by scraping. The coated sample is placed in a blast oven for drying at a temperature of 60°C. After drying for 6 hours, a nano-composite coating of a certain thickness is formed on the foam surface to obtain a flame-retardant rigid polyurethane foam.
[0067] As a comparison, hybrid nanomaterials loaded with metal Mo and Ni and hybrid nanomaterials loaded with metal Mo and Ni by BN and HNTs were mixed with polyhydroxy flame-retardant copolymers to prepare flame-retardant nanocomposite coatings. The flame-retardant rigid polyurethane foams coated with flame-retardant nanocomposite coatings were named Mo-BN, Ni-BN, Mo-HNTs and Ni-HNTs samples for testing and comparison. Among them, the loading amount of the hybrid nanomaterial was 10wt%, the mass ratio of the hybrid nanomaterial to the polyhydroxy flame-retardant copolymer was 1:20, and the solid content of the loading was 5g / dm 3 .
[0068] from Figure 6 and Figure 7 It can be seen that all flame retardant coatings showed inherent flame retardancy in the microcalorimeter (MCC) test, and the peak heat release rate (PHRR) and total heat release rate (THR) values were reduced compared with the flame retardant rigid polyurethane foam coated with only polyhydroxy flame retardant copolymer. The Ni-HNTs sample had the lowest PHRR value of 57.8 W g -1 , the THR value is only 5.03 kJ g -1 At 35kW, the pHRR of the prepared coating decreased by up to 45.0%, and the THR decreased by up to 31.1%. The MCC test showed that the addition of inorganic materials has a synergistic flame retardant effect on the entire system, which is of great significance for reducing polymer combustion and avoiding serious fire hazards.
[0069] In addition, the combustion behavior of flame-retardant rigid polyurethane foam under different thermal radiation powers (35 kW, 50 kW and 70 kW) was also analyzed ( Figure 8, 9, 10). Under thermal radiation, pure RPUF burns quickly and violently. The PHRR of pure RPUF is 282.2 kW / m 2 , corresponding to the thermal decomposition and rapid combustion of RPUF, the THR of pure RPUF is 56.6 MJ / m 2 . The ignition time of the coated RPUF was significantly prolonged compared with that of the RPUF, at least by 10 s. All treated samples showed a significant decrease in the peak heat release rate (PHRR), indicating that the coating promoted the formation of char, formed a dense and complete char layer, suppressed the heat release and protected the underlying matrix. The PHRRs of Mo-BN, Ni-BN, Mo-HNTs and Ni-HNTs were 204.2, 160.2, 183.1 and 142.5 kWm, respectively. -2 . However, the reduction in THR of the treated samples was not obvious, only 5%-10%. The main reason for this is that the thermal decomposition of the coating itself releases heat, which also prolongs the smoldering time of the foam, resulting in the continuous heat release modified foam still showing excellent fire resistance under higher power thermal radiation, which can meet the requirements of different application scenarios. The PHRR and THR values of the modified samples were also significantly reduced, indicating that the synthesized coating has an excellent flame retardant effect. In addition, the total smoke production (TSP) of the coated foam was significantly reduced, and both CO and CO2 emissions were reduced, indicating that the coating has a certain smoke suppression effect. For higher thermal radiation (50 and 70 kW), the synthesized coating has lower TSP values and lower CO emissions, and also has a better smoke suppression effect.
[0070] In addition, smoke density tests were conducted ( Fig.11 ), the smoke exhaust effect of pure RPUF and treated samples was further evaluated. Pure RPUF produced a large amount of smoke during the test, and the smoke density curve of RPUF rose rapidly within 150s, reaching a maximum Ds value of 110.4. In contrast, the flame retardant coating-modified foam released less smoke during the entire test period, indicating that the coating has a significant smoke suppression effect during combustion. The maximum Ds values of Mo-BN, Ni-BN, Mo-HNTs and Ni-HNTs samples were significantly reduced, and the minimum Ds of the Ni-HNTs sample was reduced by 83.5%. In the smoke toxicity analysis ( Fig.12 ), it was found that the Ds value of H2O increased significantly, and the Ds value of CO decreased significantly, indicating that the synthesized organic-inorganic hybrid coating is effective in inhibiting smoke release and reducing smoke toxicity. Metal (Mo and Ni) nanoparticles doped in the coating promote the conversion of CO into CO2, and the Ds value is low.
[0071] Figure 1This is the NMR spectrum of the polyhydroxy flame retardant copolymer prepared by addition polymerization of sodium styrene sulfonate and hydroxybutyl acrylate in Example 1, demonstrating the successful synthesis of the polyhydroxy flame retardant copolymer.
[0072] Figure 2 This is the NMR spectrum of the polyhydroxy flame retardant copolymer prepared by addition polymerization of sodium styrene sulfonate and hydroxypropyl methacrylate in Example 2, demonstrating the successful synthesis of the polyhydroxy flame retardant copolymer.
[0073] Figure 3 This is a scanning electron microscope image of the transition metal oxide-loaded halloysite nano (HNTs) hybrid material prepared by the impregnation method in Example 5, showing that the transition metal oxide is successfully loaded on the surface of the rod-shaped nanotubes.
[0074] Figure 4 This is a transmission electron micrograph of the transition metal oxide-loaded halloysite nano (HNTs) hybrid nanomaterial prepared by the impregnation method in Example 5, showing the loading of the transition metal oxide on the surface of the rod-shaped nanotubes.
[0075] Figure 5 This is the X-ray diffraction pattern of the hybrid nanomaterial of hexagonal boron nitride and halloysite nanotubes prepared by the impregnation method in Example 5, showing the crystal form and structure of the transition metal oxide after being loaded on the surface of hexagonal boron nitride and halloysite nanotubes.
[0076] Figure 6 The results of the microcalorimeter test at 35 kW for the rigid polyurethane foam with the flame-retardant nanocomposite coating prepared in Example 6 show that the pHRR is reduced by 45.0% at the maximum and the THR is reduced by 31.1% at the maximum, which proves that the addition of inorganic materials has a synergistic flame retardant effect.
[0077] Figure 7 The results of the microcalorimeter test at 50 kW for the rigid polyurethane foam with the flame-retardant nanocomposite coating prepared in Example 6 show that the pHRR is reduced by 43.8% at the maximum and the THR is reduced by 19.8% at the maximum, which proves that the addition of inorganic materials has a synergistic flame-retardant effect.
[0078] Figure 8 The cone calorimeter test results of the rigid polyurethane foam with the flame-retardant nanocomposite coating prepared in Example 6 at 35 kW show that the THR is reduced by up to 65.1%, and the TSP is reduced by up to 17.9%.
[0079] Fig. 9 The cone calorimeter test results of the rigid polyurethane foam with the flame-retardant nanocomposite coating prepared in Example 6 at 50 kW show that the THR is reduced by up to 26.1%, and the TSP is reduced by up to 49.3%.
[0080] Fig.10The cone calorimeter test results of the rigid polyurethane foam with the flame-retardant nanocomposite coating prepared in Example 6 at 75 kW show that the THR is reduced by up to 37.5%, and the TSP is reduced by up to 48.2%.
[0081] Fig.11 This is the smoke test result of the rigid polyurethane foam with the flame-retardant nanocomposite coating prepared in Example 6 at 25 kW, and Ds is reduced by up to 83.5%.
[0082] Fig.12 The toxicity test results of the rigid polyurethane foam with the flame-retardant nanocomposite coating prepared in Example 6 at 25 kW are as follows: CO is reduced by up to 52.6%, and H2O is increased by up to 98%.
[0083] Fig.13 This is a scanning electron microscope image of the carbon residue after combustion of the rigid polyurethane foam with the flame-retardant nanocomposite coating prepared in Example 6, which proves the high-efficiency flame-retardant and smoke-suppressing ability of the flame-retardant coating.
Claims
1. A method for preparing a highly efficient organic-inorganic hybrid fire retardant coating, characterized in that The steps include: Step 1: Preparation of polyhydroxy flame retardant copolymer The hydroxyl-containing biomass molecules are slowly added dropwise to an aqueous solution of sodium styrene sulfonate, and heated to react under stirring, and then a deionized aqueous solution of potassium persulfate is added dropwise to the system to prepare a polyhydroxy flame-retardant copolymer, and the remaining monomers and excess water are removed by dialysis and drying; Step 2: Loading of transition metal oxides The metal salt precursor is dispersed in deionized water, hexagonal boron nitride or halloysite nanotubes are added, ammonia water is used as a precipitant, and the reaction is stirred at room temperature to complete the loading of the active component; after the reaction is completed, centrifugation, washing and drying are performed, and hexagonal boron nitride loaded transition metal oxide nanomaterials or halloysite nanotube loaded transition metal oxide nanomaterials are obtained after calcination; Step 3: Preparation of composite coating Using deionized water as a dispersion medium, hexagonal boron nitride-loaded transition metal oxide nanomaterials and / or halloysite nanotube-loaded transition metal oxide nanomaterials are added to the polyhydroxy flame-retardant copolymer obtained in step 1 by solution mixing to obtain an organic-inorganic hybrid coating slurry; the obtained coating slurry is applied to the surface of a base material, and a flame-retardant nanocomposite coating is obtained after drying.
2. The preparation method according to claim 1, characterized in that: In step 1, the hydroxyl-containing biomass molecule is hydroxybutyl acrylate or hydroxypropyl methacrylate.
3. The preparation method according to claim 1, characterized in that: In step 1, the feed ratio of hydroxyl-containing biomass molecules to sodium styrene sulfonate is in the range of 0.5:1-1:1, and the feed ratio of sodium styrene sulfonate to potassium persulfate is in the range of 80:1-100:
1.
4. The preparation method according to claim 1, characterized in that: Step 1, the size of the dialysis bag is 36mm-70mm, the solid content of the polyhydroxy flame retardant copolymer obtained by dialysis is 10-30wt%, and the number average molecular weight of the obtained polyhydroxy flame retardant copolymer is controlled between 200000-300000.
5. The preparation method according to claim 1, characterized in that: In step 2, the metal salt precursor is one or more of nickel chloride and sodium molybdate; the concentration of the metal salt precursor solution is in the range of 0.5 mol / L-1 mol / L.
6. The preparation method according to claim 1, characterized in that: In step 2, the content of the transition metal oxide in the carrier is in the range of 5wt%-10wt%, and the transition metal oxide is one of nickel oxide and molybdenum oxide.
7. The preparation method according to claim 1, characterized in that: In step 2, the size of hexagonal boron nitride is controlled within the range of 1-30 μm; the diameter of the halloysite nanotube is within the range of 50-200 nm, and the length is within the range of 200 nm-1 μm.
8. The preparation method according to claim 1, characterized in that: In step 3, the ratio of the mass of the hexagonal boron nitride-loaded transition metal oxide nanomaterial and / or the halloysite nanotube-loaded transition metal oxide nanomaterial to the mass of the polyhydroxy flame-retardant copolymer is 1:10 to 1:
20.
9. Use of the organic-inorganic hybrid fire-retardant coating prepared by the preparation method according to any one of claims 1 to 8 in the preparation of a flame-retardant rigid polyurethane foam material, characterized in that: With rigid polyurethane foam as the base material, the organic-inorganic hybrid coating slurry is coated on the surface of the base material, and after drying, a flame-retardant rigid polyurethane foam material can be obtained.
10. The use according to claim 9, characterized in that: The solid content of the coating on the substrate surface ranges from 3 g / dm 3 -6 g / dm 3 .
Citation Information
Patent Citations
Method for preparing flame-retardant soft polyurethane foam
CN116284988A
High-flame-retardant rigid polyurethane foam thermal insulation material and preparation method thereof
CN118005882A
Flame-retardant water-based emulsion for coating glass fiber sleeve and preparation method of emulsion
CN103804570A
Flame-retardant microcapsule and preparation method thereof
CN111589388A
Organic phosphonic acid metal salt flame-retardant composition coating as well as preparation method and application thereof
CN115595033A